Gas exchange and water stress index in soybean cultivated under water deficit and soil compaction - Alves da Silva, Jodean; Gonsaga de Carvalho, Luiz; Ribeiro Andrade, Fabrício (Revista Ceres, 2022)
Water stress is intrinsically related to soil water availability which is determinant in gas exchanges, as well as soil compaction in soybean growth and development. This study aimed to evaluate the leaf gas exchange, water stress index, and dry mass accumulation of soybean cultivated in different daily irrigation depths and bulk density. The treatments were distributed in pots subdivided in a 4×4 factorial scheme: four levels of bulk density of the soil (1.0, 1.15, 1.30 and 1.45 g cm-3) and four daily irrigation depths (4.0, 5.0, 6.0- and 7.0-mm day-1), with three replications. Physiological and morphological variables were analyzed. There were low transpiration rates due to water deficit in the 4 mm daily irrigation depth that resulted in stomatal closure and impaired the performance of the photosynthetic process in soybean. The increase in soil density provided gains in shoot and dry root mass in the layer above the compacted one. Low availability of water in the soil reduces the photosynthesis and growth of soybean plants. Increase in bulk density of the soil promotes greater root development, with the layer above the compacted being the one that concentrates most of the roots.